2000
DOI: 10.1002/1096-9861(20010115)429:3<455::aid-cne7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic correlates of the face and oral cavity representations in the somatosensory cortical area 3b of monkeys

Abstract: We determined the somatotopy of the face and the oral cavity representation in cortical area 3b of New World owl monkeys and squirrel monkeys. Area 3b is apparent as a densely myelinated strip in brain sections cut parallel to the surface of flattened cortex. A narrow myelin-light septum that we have termed the "hand-face septum" separates the hand representation from the more lateral face and mouth representation. The face and oral cavity representation is further divided into a series of myelin-dense ovals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 63 publications
(107 reference statements)
9
108
1
1
Order By: Relevance
“…The recordings in squirrel and owl monkeys (Jain et al, 2001), as well as those more recently in galagos (data not shown), revealed additional representations of the tongue and teeth in cortex adjoining area 3b (Fig. 1).…”
Section: Representation Of Tongue and Teeth In Area 3b And Adjoining supporting
confidence: 57%
See 2 more Smart Citations
“…The recordings in squirrel and owl monkeys (Jain et al, 2001), as well as those more recently in galagos (data not shown), revealed additional representations of the tongue and teeth in cortex adjoining area 3b (Fig. 1).…”
Section: Representation Of Tongue and Teeth In Area 3b And Adjoining supporting
confidence: 57%
“…However, later it became apparent that the histological boundaries of area 3b were quite visible in appropriately stained sections cut parallel to the cortical surface after cortex had been artificially flattened so that dorsomedial and ventrolateral portions of area 3b were forced into the same plane (Tootell et al, 1985). Such brain sections in owl and squirrel monkeys revealed that area 3b extends much further rostrally than ever suspected, and that the myelin-dense architecture of area 3b contains a number of interruptions that relate to somatotopy (Jain et al, 2001). First, there is a long mediolateral band of dense myelination that extends from near the medial wall to near the lateral fissure.…”
Section: Representation Of Tongue and Teeth In Area 3b And Adjoining mentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical magnification: Although somatosensory cortical magnification factors (CMF, mm cortex/mm skin) in non-human primates have been studied extensively [19,20,[22][23], few data exist on somatosensory CMFs in the human, especially at the sub-millimeter scale. We estimated a CMF of 0.36 mm/cm of facial skin.…”
Section: Discussionmentioning
confidence: 92%
“…This "hand-face border" can be detected as a myelin-light septum in brain sections cut parallel to the cortical surface. Further laterally, myelin-dense ovals were shown to indicate anatomical modules that correspond to representations of different orofacial structures in both New [16,17] and Old World monkeys [13,15]. In New World monkeys, the myelin-dense ovals are arranged in a rostrocaudal direction and extend to the ventral frontal lobe.…”
Section: Representation Of Orofacial Structures In Area 3bmentioning
confidence: 95%